2018
DOI: 10.1111/jora.12342
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Counterfactual Emotions After Risky Decisions in Late Adolescents and Young Adults

Abstract: Adolescents' neural substrates of emotional reactions to the consequences of risky decisions are poorly understood. In this functional magnetic resonance imaging study, 30 late adolescents and 30 young adults made risky and neutral decisions in social scenarios and received valenced outcomes. Negative outcomes in risky decisions eliciting regret, as compared with negative outcomes in neutral decisions eliciting disappointment, activated executive control (orbitofrontal cortex) and self-relevance regions (middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…This increased vulnerability seems to be due to an asynchrony in brain development, in which the subcortical limbic system presents a more accelerated development than the orbitofrontal zone. [17][18][19] This asynchrony means that when an emotional stimulus is presented, adolescents manifest a higher level of activation in brain areas associated with socioemotional aspects and lower activation in areas related to cognitive control. Rational decision-making is disadvantaged while risk behaviours might be increased by sensation seeking and emotional dysregulation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This increased vulnerability seems to be due to an asynchrony in brain development, in which the subcortical limbic system presents a more accelerated development than the orbitofrontal zone. [17][18][19] This asynchrony means that when an emotional stimulus is presented, adolescents manifest a higher level of activation in brain areas associated with socioemotional aspects and lower activation in areas related to cognitive control. Rational decision-making is disadvantaged while risk behaviours might be increased by sensation seeking and emotional dysregulation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Several studies have shown that adolescents have biological limitations to balance emotions and rationality during decision-making. This increased vulnerability seems to be due to an asynchrony in brain development, in which the subcortical limbic system presents a more accelerated development than the orbitofrontal zone 17–19. This asynchrony means that when an emotional stimulus is presented, adolescents manifest a higher level of activation in brain areas associated with socioemotional aspects and lower activation in areas related to cognitive control.…”
Section: Introductionmentioning
confidence: 99%
“…They find that although behavioral performance on a response inhibition task did not predict sexual risk, adolescents who needed to recruit more middle frontal gyrus activation on the task made riskier sexual decisions, such as reduced use of condoms. Another study in this special section, Rodrigo, Padrón, de Vega, and Ferstl () focuses on emotional responding during risky decision making. This study demonstrates the importance of taking a more nuanced view of emotion by focusing on neural circuits involved in the experience of counterfactual emotions, such as regret and disappointment, during a social decision‐making task.…”
Section: Key Themes Explored In This Special Sectionmentioning
confidence: 99%
“…The articles in this special section nicely exemplify the strengths of applying neuroscience to psychopathology, as adolescence is a period at which many of these problems manifest themselves. All of the articles focus on patterns of functional activation associated with potential emotional and behavioral difficulties, including externalizing and conduct disorder behaviors (Brieant et al, 2018;Saxbe et al, 2018;Schriber et al, 2018;Trucco, Cope, Burmeister, Zucker, & Heitzeg, 2018), risky decision making (Hansen, Thayer, Feldstein-Ewing, Sabbineni, & Bryan, 2018;Rodrigo, Padr on, de Vega, & Ferstl, 2018), stress responsivity (T.-H. Lee, Qu, & Telzer, 2018), and depression symptomatology (K. H. Lee, Oppenheimer, et al, 2018). Recent calls have been made to build upon these insights and expand the field's scope to understanding normative processes, puberty, and the unique opportunities for positive development afforded by brain development during adolescence (Crone & Dahl, 2012;Pfeifer & Blakemore, 2012).…”
Section: An Integrative Approach That Incorporates Both Typical and Amentioning
confidence: 99%
“…Collectively, the articles in the section include an impressive amount of diversity in their samples, including notable numbers of U.S. adolescents from Latino, European American, and African American backgrounds. Only one study, however, included participants from outside of the United States (Rodrigo et al., ). None of the studies focused on substantive topics related to population diversity, which is not a problem in itself because diverse samples need to be included in studies of basic psychological and behavioral development.…”
Section: Attention To Population Diversity According To Ethnicity Andmentioning
confidence: 99%